Analyzing issues and challenges on environmentally supportive behaviour among Malaysian and Nigerian consumers - Ogiemwonyi, Osarodion; Harun, Amran; Othman, Bestoon; Ismael, Darbaz; Alam, Mohammad Nurul; Hamawandy, Nawzad Majeed (Publication International Lahore, 2020)
The study reviews and highlights the influence of environmentally supportive behaviour among Malaysian and Nigerian consumers. The review identifies various barriers with emphases on the issues and challenges affecting both nations and how the barriers can be stopped. Based on the conceptual review, the study concludes that there is still an inappropriate strategy for the implementation of green behaviour in emerging nations. Specifically, there is a gap in awareness, education, negative perception, distrust of green claims and behaviour among green consumers. The study further argues that institutional and cultural differences impact consumers in both nations. If individual citizens could participate fully or embrace environmentally supportive behaviour, the nature and humanity can be saved from the environmental threat and pitfall. Suggestions included in this study is aimed to help green managers formulate an appropriate strategy to encourage sustainable lifestyle and behaviour.